The scientific integrity of ADHD: A critical examination of the underpinning theoretical constructs - Mills, Sheelah (Frontiers in Psychiatry, 2022)
Prior to the establishment and promotion of ADHD as a psychiatric disorder, the labels “minimal brain dysfunction” (MBD), “hyperactivity” (HA), and “learning disability” (LD) were diagnostic terms for children with hard-to-manage behaviors. At the time, these labels and the treatment interventions, especially the heavy reliance on stimulant medications, were subject to criticism. Nearly half a century later, these criticisms apply equally to ADHD, suggesting a disturbing lack of progress in this area of child psychiatry. Therefore, the aim of this article is to examine the scientific integrity of ADHD, to establish why this is the case. I use a philosophy of science framework to track the initial thinking, the plausibility, and the acceptance of ADHD. I establish that ADHD, along with the evolving biomedical model for psychiatry, was accepted in the third edition of the American Psychiatric Association's (APA) Diagnostic and Statistical Manual (DSM-III) as the result of bias and compromise between theorists' of different persuasions. Although initial ideas are expected to be subjective, they also need to demonstrate plausibility prior to empirical investigation. Research from the disciplines of biological psychiatry and cognitive psychology influenced the creation of ADHD, so I critically examine specific ideas that underpinned these disciplines at that time. I find these to be implausible and not congruent with current scientific knowledge, this extends to more recent theory. I conclude there is little good reason to consider DSM-III's concept of ADHD as empirically confirmed, nor do I find good reason to expect such confirmation will be forthcoming.